2014
DOI: 10.3389/fcimb.2014.00059
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing 16S rRNA genes of bacteria associated with wild tiger mosquito Aedes albopictus: a pilot study

Abstract: The Asian tiger mosquito Aedes (Stegomya) albopictus is an invasive species that has spread across the world in the last two decades, showing a great capacity to adapt to contrasting climates and environments. While demonstrated in many insects, the contribution of bacterial symbionts in Aedes ecology is a challenging aspect that needs to be investigated. Also some bacterial species have already been identified in Ae. albopictus using classical methods, but a more accurate survey of mosquito-associated bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 49 publications
4
47
0
Order By: Relevance
“…Those that applied the culture‐independent deep sequencing approach were mainly restricted to gut bacterial communities (Minard et al., 2012; Wang, Gilbreath, Kukutla, Yan, & Xu, 2011) or other isolated adult arthropod parts (Damiani et al., 2010; Sharma et al., 2014), although one study investigated bacteria diversity from whole Ae. albopictus (Minard et al., 2014). Studies using shotgun metagenomic sequencing (which is agnostic to the genetic material sequenced, as opposed to the gene‐specific amplicon‐based method used here) have identified both bacterial and eukaryotic microbes associated with mosquitoes, however with insufficient depth to perform diversity analyses (Chandler, Liu, & Bennett, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Those that applied the culture‐independent deep sequencing approach were mainly restricted to gut bacterial communities (Minard et al., 2012; Wang, Gilbreath, Kukutla, Yan, & Xu, 2011) or other isolated adult arthropod parts (Damiani et al., 2010; Sharma et al., 2014), although one study investigated bacteria diversity from whole Ae. albopictus (Minard et al., 2014). Studies using shotgun metagenomic sequencing (which is agnostic to the genetic material sequenced, as opposed to the gene‐specific amplicon‐based method used here) have identified both bacterial and eukaryotic microbes associated with mosquitoes, however with insufficient depth to perform diversity analyses (Chandler, Liu, & Bennett, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…quinquefasciatus (Werren, Baldo, & Clark, 2008). Other bacterial taxa, such as Providencia and Erwinia (all Family Enterobacteriaceae), are commonly identified with Aedes, Culex , and other mosquitoes (Demaio, Pumpuni, Kent, & Beier, 1996; Minard et al., 2012, 2014; Rani, Sharma, Rajagopal, Adak, & Bhatnagar, 2009; Zouache, Michelland, Failloux, Grundmann, & Mavingui, 2012). Likewise, the most common eukaryotic microbes identified in this study have also been previously found associated with mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies exploiting high throughput sequencing have revealed that the bacterial microbiome of mosquito vectors has low diversity but is highly variable. Most studies thus far have focused on Anopheles mosquitoes [4 • ,5,6 • ,7 •• ,8 •• ,9], and while the number of studies examining the bacterial microbiomes from Aedes and Culex mosquitoes is growing [6 • ,8 •• ,10], this is an area that needs further attention. Although not as comprehensive, culture dependent approaches have been used for characterization of the microbiome of important Aedes and Culex arboviral vectors [11,12].…”
Section: Composition Of the Mosquito Microbiomementioning
confidence: 99%